Choroidal Thickness in Different Types of Inherited Retinal Dystrophies. - Sabbaghi, Hamideh; Ahmadieh, Hamid; Jalili, Jalil; Behnaz, Nazanin; Fakhri, Maryam; Suri, Fatemeh; Kheiri, Bahareh; Rajabpour, Mojtaba; Entezari, Morteza; Daftarian, Narsis (Journal of Ophthalmic & Vision Research, 2020)
Purpose: To compare the choroidal thickness among eyes with retinitis pigmentosa (RP), Stargardt disease, Usher syndrome, cone-rod dystrophy, and healthy eyes of sex- and age-matched individuals. Methods: In this comparative study, 503 eyes with RP (n = 264), cone-rod dystrophy (n = 109), Stargardt disease (n = 76), and Usher syndrome (n = 54) were included. To validate the data, 109 healthy eyes of 56 sex- and age-matched individuals were studied as controls. Choroidal imaging was performed using enhanced depth imaging-optical coherence tomography. Choroidal thickness was measured manually using MATLAB software at 13 points in nasal and temporal directions from the foveal center with the interval of 500 pm and the choroidal area encompassing the measured points was calculated automatically. Results: The mean age was 36.33 ± 13.07 years (range, 5 to 72 years). The mean choroidal thickness at 13 points of the control eyes was statistically significantly higher than that in eyes with RP (P < 0.001) and Usher syndrome (P < 0.05), but not significantly different from that in eyes with Stargardt disease and cone-rod dystrophy. Among different inherited retinal dystrophies (IRDs), the choroidal thickness was the lowest in eyes with RP (P < 0.001). Choroidal thickness in the subfoveal area correlated negatively with best-corrected visual acuity (r = -0.264, P < 0.001) and the duration of ocular symptoms (r = -0.341, P < 0.001) in all studied IRDs. No significant correlation was observed between the subfoveal choroidal thickness and central macular thickness (r = -0.24, P = 0.576). Conclusion: Choroidal thinning in four different types of IRDs does not follow a similar pattern and depends on the type of IRD and the duration of ocular symptoms. A larger cohort is required to verify these findings.